Review of anthrax: A disease of farm animals - Alam, Md Emtiaj; Kamal, Md Mostofa; Rahman, Moizur; Kabir, Aurangazeb; Islam, Md Shafiqul; Hassan, Jayedul (Journal of Advanced Veterinary and Animal Research, 2022)
Anthrax is a rapidly fatal infectious disease affecting herbivores and people. In the farm animals, cattle and sheep are more susceptible, followed by goats and horses, while dwarf pigs and Algerian sheep are relatively resistant. Bacillus anthracis, the causative agent of anthrax, produces spores and persists for decades in the soil, initiating an outbreak through a favorable climate shift. Anthrax is enzootic in many Asian and African countries, and is reported in Australia, some parts of Europe, and America. The clinical courses of this disease in animals are per acute, acute, subacute, and chronic forms. In severely infected cases, the animals are dead without premonitory clinical signs. The blood may fail to clot and can be found in the mouth, nostrils, and anus in the animals that die from anthrax. This bacterium is susceptible to many antibiotics, yet only penicillin and oxytetracycline have the most effective under field conditions. When an outbreak occurs in a defined area, it is necessary to take early steps to break the infection cycle by maintaining strict biosecurity and vaccinating uninfected animals. This disease is still a challenge to farm animal production in many countries. This review intends to give a fair knowledge of the etiology, epidemiology, pathogenesis, clinical presentation, diagnosis, treatment, and control of this disease. J. Adv. Vet. Anim. Res., 9(2): 323–334, June 2022 http://doi.org/10.5455/javar.2022.i599